Estrategias de construcao da marca Yamaha no Brasil - Colombo, Caio Prisco da Silva Telles Nunes Ranieri (2006)
Objective: Understand how the japanese brand Yamaha worldwide motorcycle and scooter maker construct its corporate brand among the brazilian target-costumer, with publicities released in the Moto magazine in 2005. Justification: The importance of branding studies in the corporate market on the 21th century. Hipothesis: The power of Yamaha brand has its origin in the construction of symbolic and intangible values attributed or associated to the company and its products. Methodology: Peircean semiotics. Results: The hipothesis was confirmed. The power of Yamaha brand in the brazilian market results from the symbolic values attributed to the company it self by publicity